2016
DOI: 10.13005/bbra/2155
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Sensorial and Microbiological Properties of Mishti Dahi Supplemented with Flax Lignan During Storage and its Antidiabetic Activity

Abstract: Extensive research on lignan has revealed numerous nutritional and health benefits due primarily to its nutrients content. Flaxseed is the richest source of lignan, so flax lignan was used for the investigation. The objective of this study was to evaluate the effect of 3.75 % flax lignan supplementation on the physicochemical, microbiological and sensorial properties of mishti dahi during storage. Mishti dahi with 3.75 % flax lignan was prepared by replacing sugar with 10 % honey. There were no such difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Recent research has shown that adding flaxseed to fermented milk decreases sensory scores, but adding flaxseed extract (1-3%) to kefir did not affect sensory scores, which was consistent with our findings [30]. Another study discovered no sensory differences between flaxseed lignan-supplemented misti dahi and the control [31]. Thus, adding flaxseed as whole flaxseed powder or oil negatively affects dairy products' sensory qualities, while adding flaxseed extract does not.…”
Section: Physico-chemical Textural Sensory and Microbiological Attrib...supporting
confidence: 90%
“…Recent research has shown that adding flaxseed to fermented milk decreases sensory scores, but adding flaxseed extract (1-3%) to kefir did not affect sensory scores, which was consistent with our findings [30]. Another study discovered no sensory differences between flaxseed lignan-supplemented misti dahi and the control [31]. Thus, adding flaxseed as whole flaxseed powder or oil negatively affects dairy products' sensory qualities, while adding flaxseed extract does not.…”
Section: Physico-chemical Textural Sensory and Microbiological Attrib...supporting
confidence: 90%